2011
DOI: 10.4081/hr.2011.e21
|View full text |Cite
|
Sign up to set email alerts
|

The OnControl Bone Marrow Biopsy Technique Is Superior to the Standard Manual Technique for Hematologists-In-Training: A Prospective, Rrandomized Comparison

Abstract: The purpose of this study was to compare a novel bone marrow device with the standard marrow needle in a prospective, randomized study in a teaching hospital employing hematologists-in-training. The new device, the OnControl Bone Marrow (OBM) Biopsy System, utilizes a battery-powered drill to insert the needle. Fifty-four bone marrows (27 standard and 27 OBM) were performed by 11 fellows under the observation and supervision of 3 attending hematologists and 1 research technologist. The primary endpoint of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 9 publications
(19 reference statements)
3
37
0
Order By: Relevance
“…As an alternative, a novel coaxial biopsy system powered by a handheld drill (OnControl; Vidacare Corporation, Shavano Park, TX, USA) has recently been introduced. Initial studies showed that iliac bone marrow aspiration and core biopsy could be performed safely and in less time with this drill-powered device compared with traditional manual devices, and that specimens obtained using the drill were histologically adequate [3][4][5][6]. Similar results were subsequently reported for CT-guided percutaneous bone biopsies of the axial and appendicular skeleton [7,8].…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…As an alternative, a novel coaxial biopsy system powered by a handheld drill (OnControl; Vidacare Corporation, Shavano Park, TX, USA) has recently been introduced. Initial studies showed that iliac bone marrow aspiration and core biopsy could be performed safely and in less time with this drill-powered device compared with traditional manual devices, and that specimens obtained using the drill were histologically adequate [3][4][5][6]. Similar results were subsequently reported for CT-guided percutaneous bone biopsies of the axial and appendicular skeleton [7,8].…”
Section: Introductionsupporting
confidence: 54%
“…This was previously demonstrated with iliac wing bone marrow core biopsies [5], and this study shows similar results when obtaining vertebral body specimens. However, the higher yield obtained may be offset by the presence of crush artifact likely introduced by the power generated by drill assistance [3]. Crush artifact was present in three specimens (11 %; 3/28), which in one case (3.6 %; 1/28) precluded definitive diagnosis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We did not experience any device-related complications, which is in line with other reports using the OBM for other indications [10][11][12]. There are no device-related safety issues to be mentioned beside the fact that the OBM might not be recharged but has to be exchanged when the battery is empty.…”
Section: Discussionsupporting
confidence: 90%
“…The device allows to obtain large core specimen and handling has been shown to be easy to learn for hematologists in training, e.g., to perform bone biopsies of the iliac crest and subsequent bone marrow aspiration [10,11]. The drill has been proven to be safe to handle also under CT guidance to acquire evaluable bone specimens for histopathologic workup in oncologic patients [12].…”
Section: Introductionmentioning
confidence: 99%